(untitled) (Triyuga Academic Journal, 2024)
English is a popular language in Nepal. Its use is increasing day by day. English in Nepal is used as the foreign language but its importance is not less than that of second language. This study reports on the growing popularity of English language in Nepali academia, socio-economic as well as political showground. Further, the study explores that English in the past was called elites’ language, however this notion has been changed and now it has become everyone’s language. The study was conducted using archived resources such as journals, articles and books. Findings of the study highlight the past history, present situation and future prospect of English language in Nepal with the conclusion that English language has become everybody’s language from the elites’ language.